Таксономия Блума – эффективный инструмент управления процессом обучения - Мурзагалиева, А.Е. (My University, 2016)
Core competencies of the graduate school presuppose the existence of basic literacy, combined with a high level of thinking. The task of the teacher today is not to supply the student the sum of knowledge, and in arming a tool that can be used to obtain this knowledge yourself. This task of the teacher may decide to Bloom's taxonomy.
Keywords: thinking; goal; action; result